Art collection study Light level, texture and color - Singson, Millicent Hernandez (Quezon City, 2011)
The Jorge B. Vargas house different art collection such as oil paintings, watercolors, pastels, drawings, and sculptures. This theses focused on the permanent artworks on display in the Main Gallery of the Vargas Museum and on the artistic components of Fernando Amorsolo paintings, that is, texture and color.

The first study aimed to address the excessive light exposure that can cause extreme and irreversible damage to the permanent collections in the Main Gallery. Two different light level assessments are conducted, specifically, light level on each artwork at different time interval and when different light sources are present in the gallery. After the assessments, locations wherein artworks are at greater risk of light damage are identified. Furthermore, the factors affecting the light level in the Main Gallery of the museum are identified to be the architecture of the gallery, the solar path with respect to the artworks, and the location of the artworks in the gallery. These mentioned factors are important to be taken into account by the Vargas Museum management in the installation of their exhibits.

The study for texture is an investigation on how to improve the 3-D reconstruction of a surface using photometric stereo. Particularly, the study solved the global flateness problem encountered when using the technique on painting surfaces by reconstructing the whole image by section. A method is introduced on how the direction of illumination on a surface can be estimated from the shadow information. Also, limitation n the set-up and algorithms were identified.

For color, the reflectance spectra of Amorsolo's portrait paintings throughout the years were examined with the main objective of identifying Amorsolo's historical choice of color in his career and determining if this can be used to assist in the authentication of his other paintings. A manual spectrometry scanning setup is built to assist in the database spectra. Provided with the reflectance spectra, C.I.E. xy and a*b* chromaticity coordinates were calculated to assist in the analysis of color. It has been shown that it is possible to distinguish artists based on the characteristics of the reflectance spectra. The C.I.E xy chromaticity diagram provided a snapshot on the range of colors Amorsolo used in his portrait paintings. Lastly, it was found that the centroid clustering in the C.I.E. a*b* diagram cannot strongly identify any trend based on the significance of year of creation, portrait subject and gender of subject.


PACS: 42.70.Gi Light sensitive materials. 88.05.Tg Energy use in lighting. 88.40mx Day lighting/natural lighting of buildings, 07.05Pj Image Processing algorithms, Photometric Stereo, 78.40.-q Reflection spectra, 07.60.Dq Colorimeters, 07.60.Rd visible and ultraviolet spectrometer.
Undergraduate Thesis (Bachelor of Science in Applied Physics) -- National Institute of Physics, College of Science, University of the Philippines, Diliman, Quezon City
Keywords: Singson, Millicent Hernandez; Examination and conservation of works of art